Composite fiber antibacterial bandage and preparation method thereof

By co-spinning of antibacterial fibers and antibacterial fibers in the bandage, and through physical crosslinking and covalent combination technology, the problem of degradation of antibacterial properties in the antibacterial bandage is solved, and the long-lasting antibacterial and antibacterial effects of the bandage are achieved, and its strength and elasticity are improved.

CN119754018AActive Publication Date: 2025-04-04ZHEJIANG YUANLI MEDICAL TECH CO LTD

Patent Information

Application Number
CN202411959982.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

After using existing antibacterial bandages for a period of time, dead microorganisms will form biofilms on the surface of the product, hindering the contact between antibacterial agents and microorganisms, resulting in a degradation of antibacterial performance.

Method used

The bandage is prepared by co-spinning of antibacterial fibers and antibacterial fibers. By physically cross-linking the quaternary ammonium chitosan and sodium alginate, antibacterial fibers are formed, and polydopamine nanospheres are used to covalently bind with diamino polyethylene glycol to form antibacterial fibers. Finally, the antibacterial and antibacterial properties of the bandage are enhanced by the calcium chloride solution.

Benefits of technology

It achieves that the bandage prevents bacteria from adhering and reproduction during use, maintains good antibacterial effect, and gives the bandage a certain strength and elasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216860280000091
    Figure BDA0005216860280000091
  • Figure BDA0005216860280000101
    Figure BDA0005216860280000101
  • Figure BDA0005216860280000102
    Figure BDA0005216860280000102
Patent Text Reader

Abstract

The invention relates to the technical field of bandages, in particular to a composite fiber antibacterial bandage and a preparation method thereof. Carrying out physical crosslinking by utilizing the characteristics that quaternary ammonium salt chitosan is dissolved in positive charges of a water band and sodium alginate is dissolved in negative charges of the water band to obtain antibacterial impregnation liquid; by utilizing the characteristic that polyethylene glycol can effectively prevent bacteria and mould from breeding, polyethylene glycol is connected to the surfaces of the polydopamine nanospheres by adopting a covalent binding method to form a polymer molecular brush so as to obtain an antibacterial impregnation liquid; cotton fibers and polyester fibers are soaked in antibacterial impregnation liquid and antibacterial impregnation liquid respectively to obtain antibacterial fibers and antibacterial fibers, the antibacterial fibers and the antibacterial fibers are co-spun to prepare the bandage with the functions of preventing bacterial adhesion and inhibiting bacteria, and the prepared bandage has a good antibacterial effect; the antibacterial durability is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bandages, in particular to a composite fiber antibacterial bandage and a preparation method thereof. Background Art

[0002] Bandages are usually used for first aid and postoperative wound healing. They can create a clean and moist environment for the wound, provide physical support and wound protection, prevent bacterial infection and promote wound healing. In the environment where people live, floating bacteria and fungi are everywhere, and can non-specifically adhere to the interface to form biological fouling. Especially in the field of biomedicine, when these biomedical materials are used for a long time, they will cause microbial infection due to the non-specific adhesion of proteins and bacteria, which will not only prolong the wound healing time, increase the economic burden and pain of patients, but also lead to death. Usually, bacteria that are free in the air or liquid can attach to the surface of various materials that they can contact through physical adsorption, causing the initial adhesion of bacteria; as time goes on, the bacteria settled on the surface of the material resume growth and continue to proliferate; when the bacterial density reaches a certain level, the bacteria begin to continuously secrete extracellular polymers to form a biofilm matrix, and finally form a mature biofilm. At the same time, some of the detached biofilms and a small amount of released floating bacteria spread to new sites to restart the formation of biofilms. Once a biofilm is formed, it means that the bacteria have firmly adhered to the surface of the material and can protect the bacteria from being affected by environmental changes and from being killed and engulfed by antibiotics and the body's immune system. Therefore, it is necessary to study a variety of methods to prevent bacterial adhesion and reproduction, reduce bacterial adhesion from the source, and thus reduce the formation of biofilms.

[0003] A Chinese patent with announcement number CN117618624B discloses a biodegradable medical polymer bandage and a preparation method thereof, and prepares an antibacterial and skin-friendly polylactic acid. The antibacterial and skin-friendly polylactic acid is prepared by the reaction of carboxyl-modified chitosan, epoxy quaternary ammonium salt and hydrophilic-modified polylactic acid. Under the action of carboxyl-modified chitosan, the mechanical properties and hydrophilic properties of the hydrophilic-modified polylactic acid are improved, the active groups are increased, the cell adhesion ability is improved, and the application scope of PLA in the medical and health fields is expanded. The introduction of carboxyl-modified chitosan and epoxy quaternary ammonium salt improves the antibacterial and antimicrobial properties of the hydrophilic-modified polylactic acid, avoids bacterial infection of wounds, and has excellent antibacterial and antiviral effects. A Chinese patent with announcement number CN116115815B discloses an antibacterial medical bandage and a preparation method thereof. A medical non-woven fabric with good air permeability is used as a base material, which is impregnated in a thermoplastic polyurethane elastomer rubber impregnation liquid, and then a layer of uncured thermoplastic polyurethane elastomer rubber film-forming liquid is coated on the non-woven fabric with a scraper, and then a SiO2-ZnO nanoparticle dispersion is evenly coated on it, and the bandage is obtained by pressurized drying and curing.

[0004] However, the above research focuses on how to improve the antibacterial performance. However, dead microorganisms will form biofilms on the surface of fabrics, hindering the contact between antimicrobial agents and microorganisms, resulting in a decrease in antibacterial performance. Therefore, the problem that the biofilm formed by the adhesion of dead bacteria will lead to a decrease in the performance of antibacterial materials has become a focus of attention. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a composite fiber antibacterial bandage and a preparation method thereof. The antibacterial fiber and the antibacterial fiber are mixed and spun, woven, and then cross-linked with a calcium chloride solution. The prepared bandage has good antibacterial effect.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a composite fiber antibacterial bandage comprises the following steps:

[0008] S1. Preparation of antibacterial fiber: Sodium alginate is dissolved in water and then quaternary ammonium salt chitosan is added, and the mixture is reacted for 12-18 hours under magnetic stirring to obtain an antibacterial impregnation liquid, and the temperature is raised to 30-45° C., cotton fiber is added thereto to completely immerse it in the antibacterial impregnation liquid, and the cotton fiber is placed for 2-4 hours for immersion, and after the immersion is completed, the fiber is taken out and dried to obtain the antibacterial fiber; wherein the drying condition is: drying in a vacuum drying oven at 35-45° C. for 2-4 hours;

[0009] Furthermore, the preparation process of quaternary ammonium salt chitosan is as follows: using isopropanol as solvent, adding chitosan, heating and mixing uniformly, adjusting the solution pH to 8-9, then adding 2,3-epoxypropyltrimethylammonium chloride aqueous solution, heating to 75-85°C for reaction for 25-30h, and after the reaction is completed, dialyzing, filtering, and freeze-drying to obtain quaternary ammonium salt chitosan; the amount of 2,3-epoxypropyltrimethylammonium chloride in the 2,3-epoxypropyltrimethylammonium chloride aqueous solution is 0.06-0.1g / mL; the mass ratio of isopropanol, chitosan and 2,3-epoxypropyltrimethylammonium chloride is 28-32:1:4-8;

[0010] Chitosan is widely present in the carapace of marine arthropods, the carapace of insects, the cell membrane of fungi and algae, the shell and skeleton of molluscs and the cell wall of higher plants. It is a non-toxic, biodegradable and biocompatible cationic polysaccharide with a broad spectrum of antibacterial effects, which can inhibit the growth of various bacteria and fungi. Chitosan can destroy the cell membrane and cell wall of microorganisms, causing the outflow of intercellular electrolytes, causing the death of microorganisms, and can also bind to the DNA in the nucleus of microorganisms, thereby inhibiting the synthesis of RNA and protein. In addition, chitosan has the ability to promote cell regeneration, which helps the rapid healing of wounds. However, under alkaline or neutral conditions, chitosan has poor solubility, which limits its application. Quaternary ammonium compounds have low toxicity and low irritation as antibacterial agents, and are suitable for antibacterial disinfection of skin, mucous membranes and wounds. Quaternary ammonium salt has a broad-spectrum bactericidal property, and has a killing effect on various bacteria, fungi and lipophilic viruses; it is adsorbed to the surface of the thalline, and the hydrophobic group is inserted into the lipid layer, which changes the permeability of the cell membrane, destroys the membrane structure, causes the leakage of intracellular substances, and finally inhibits the cell metabolism process, causing the death of the thalline. Therefore, in the present invention, quaternary ammonium salt is utilized to modify chitosan to obtain quaternary ammonium salt chitosan as the main antibacterial agent, which further enhances the antibacterial effect. Sodium alginate is a linear macromolecular natural polysaccharide extracted from brown algae, has good bonding performance and stability, and sodium alginate has good moisture retention performance, can keep the wound surface moist environment, promote cell proliferation and tissue regeneration, and accelerate wound healing; it also has certain antibacterial and anti-inflammatory effects, reduces the risk of bacterial infection, and alleviates the inflammatory reaction around the wound surface. Quaternary ammonium chitosan molecules contain many amino groups, which are positively charged when dissolved in water, while sodium alginate is negatively charged when dissolved in water. By utilizing the positively charged characteristics of quaternary ammonium chitosan and the negatively charged characteristics of sodium alginate for physical cross-linking, the bonding strength is increased and dispersion is facilitated. Cotton textiles have good air permeability and moisture absorption capacity, and can be soft, comfortable, heat-insulating and warm in daily life applications. However, they lack antibacterial groups and do not have antibacterial ability, which can easily lead to bacterial growth during application. Therefore, in this step, quaternary ammonium chitosan is used as an antibacterial agent to combine with sodium alginate and impregnate cotton fibers to obtain antibacterial fibers with surface-coated antibacterial agents;

[0011] S2. Preparation of antibacterial fiber: adding polydopamine nanospheres to Tris buffer, adding diamino polyethylene glycol after ultrasonic dispersion, reacting for 25-30 hours under magnetic stirring to obtain antibacterial impregnation liquid, adding polyester fiber to the antibacterial impregnation liquid to make it completely immersed in the antibacterial impregnation liquid, leaving it for 2-4 hours for impregnation, taking it out and drying it after the impregnation is completed to obtain antibacterial fiber; wherein the drying condition is: drying at 35-45° C. in a vacuum drying oven for 2-4 hours; the ultrasonic dispersion condition is: ultrasonication at a power of 500 W for 6-10 minutes;

[0012] Furthermore, the preparation process of polydopamine nanospheres is as follows: adding anhydrous ethanol, ammonia water and water into a reactor, adding dopamine hydrochloride after mixing evenly, reacting at room temperature for 28-36 hours, centrifuging, and washing to obtain polydopamine nanospheres; the volume ratio of anhydrous ethanol, ammonia water and water is 3.5-5.5:0.1:8.2-12.5; the amount of dopamine hydrochloride in water is 2.2-3.0 mg / mL;

[0013] After using the existing antibacterial products for a period of time, dead microorganisms will form biofilms on the surface of the products, hindering the contact between the antibacterial agent and the microorganisms, causing the antibacterial performance of the products to gradually weaken, and the biofilm will provide new sites for the subsequent bacterial adhesion, further reducing the antibacterial effect of the products. In view of this problem, the present invention introduces antibacterial fibers and also prepares antibacterial fibers that prevent bacterial adhesion. Polydopamine nanospheres are nanoparticles prepared from polydopamine, which have dopamine functional groups, have super strong adhesion properties, good biocompatibility and multifunctionality; the dopamine functional groups on the surface of polydopamine nanospheres can interact with bacteria and microorganisms, and have the potential for antibacterial and anti-biological pollution; the molecular structure of polyethylene glycol can change the energy state of the surface, reduce the attraction of the surface of the object, and make it difficult for dirt to adhere, so polyethylene glycol can effectively prevent the growth of bacteria and mold. At the same time, polyethylene glycol is a hydrophilic substance with good moisturizing effect, and can also promote local blood circulation, stimulate collagen regeneration, and play a certain repairing role on damaged skin. Therefore, in this step, polyethylene glycol is connected to the surface of polydopamine nanospheres by covalent bonding to form a polymer molecular brush, which can effectively prevent the adhesion of bacteria and proteins. Polyester fiber has excellent wear resistance and shape retention, high strength and elastic recovery ability, but its hygroscopicity is poor and its air permeability is poor; by immersing it in an antibacterial impregnation liquid containing polydopamine nanospheres modified with diaminopolyethylenediamine, its hydrophilicity can be improved, and by co-spinning with cotton fibers with antibacterial properties, the hygroscopicity and air permeability of the bandage are further improved, while giving the bandage a certain strength and elasticity.

[0014] S3, spinning and weaving the antibacterial fiber and the antibacterial fiber together to obtain an antibacterial bandage base material, immersing it in water, adding concentrated ammonia water and quickly stirring and mixing it evenly, standing it for 25-30 hours, and then adding calcium chloride solution for cross-linking, absorbing the calcium chloride solution after 3-5 hours, soaking and washing with water, changing the water every 2-4 hours, and taking it out and drying it after changing it 3-5 times to obtain the composite fiber antibacterial bandage; the drying conditions are: drying in a vacuum drying oven at 40-50° C. for 4-8 hours;

[0015] In this step, Ca +The sodium alginate coated on the antibacterial fiber and the polydopamine nanospheres coated on the antibacterial fiber are cross-linked. At the same time, a large number of hydroxyl groups on the surface of sodium alginate and a large number of hydrogen bonds between hydroxyl groups and amino groups on the surface of polydopamine nanospheres make the molecules attract each other, forming a macromolecular network structure on the surface of the prepared antibacterial bandage, further enhancing the bonding strength between the polymer and the fiber and improving the stability of the prepared bandage.

[0016] The present invention has the following beneficial effects:

[0017] The present invention prepares a bandage with both antibacterial adhesion and antibacterial functions by co-spinning antibacterial fibers and antibacterial fibers. Quaternary ammonium chitosan is obtained by modifying chitosan with quaternary ammonium salt as the main antibacterial agent, and the antibacterial impregnation liquid is obtained by physical cross-linking using the characteristics that quaternary ammonium chitosan is positively charged when dissolved in water and sodium alginate is negatively charged when dissolved in water. The antibacterial fiber is obtained by immersing cotton fiber in the antibacterial impregnation liquid. Polyethylene glycol is connected to the surface of polydopamine nanospheres by a covalent bonding method to form a polymer molecular brush to obtain an antibacterial impregnation liquid, and the polyester fiber is immersed in the antibacterial impregnation liquid to obtain the antibacterial fiber. Finally, Ca + The sodium alginate coated on the antibacterial fiber and the polydopamine nanospheres coated on the antibacterial fiber are cross-linked to form a macromolecular network structure on the surface of the prepared antibacterial bandage, which further enhances the bonding strength between the polymer and the fiber, so that the prepared bandage has good and lasting antibacterial properties while also giving the bandage a certain strength and elasticity. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] The sodium alginate (AR) used in the present invention was purchased from Chengdu Shuobo Yanchuang Technology Co., Ltd., cotton fiber was purchased from Dezhou Caishihe Textile Co., Ltd., polyester fiber was purchased from Unijika (Shanghai) Trading Co., Ltd. (Japan UNIIKA), isopropanol, 2,3-epoxypropyltrimethylammonium chloride, Tris buffer, diaminopolyethylene glycol, dopamine hydrochloride, anhydrous ethanol, ammonia water (7.5% v / v), and calcium chloride were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (China), chitosan was purchased from Shanghai McLean Biochemical Technology Co., Ltd. (China), and concentrated ammonia water was purchased from Tianjin Damao Chemical Reagent Factory. All reagents are commonly available on the market.

[0020] Embodiment 1

[0021] A method for preparing a composite fiber antibacterial bandage comprises the following steps:

[0022] S1. Preparation of antibacterial fiber: 2 parts by weight of sodium alginate was dissolved in 185 parts by weight of deionized water, and then 3.5 parts by weight of quaternary ammonium salt chitosan was added, and the mixture was reacted for 16 hours under magnetic stirring to obtain an antibacterial impregnation liquid, and the temperature was raised to 40° C., 85 parts by weight of cotton fiber was added thereto to completely immerse the cotton fiber in the antibacterial impregnation liquid, and the fiber was placed for 3 hours for immersion, and after the immersion was completed, the fiber was taken out and dried to obtain the antibacterial fiber; the drying conditions were: drying in a vacuum drying oven at 40° C. for 3 hours;

[0023] The preparation process of quaternary ammonium salt chitosan is as follows: using isopropanol as solvent, adding chitosan, heating to 70°C and mixing for 6 hours, adjusting the solution pH to 8-9 with 1% NaOH solution, then adding 2,3-epoxypropyltrimethylammonium chloride aqueous solution, heating to 80°C and reacting for 28 hours, dialyzing for 2 days after the reaction to remove unreacted 2,3-epoxypropyltrimethylammonium chloride, filtering and freeze-drying to obtain quaternary ammonium salt chitosan; the amount of 2,3-epoxypropyltrimethylammonium chloride in the 2,3-epoxypropyltrimethylammonium chloride aqueous solution is 0.08 g / mL; the mass ratio of isopropanol, chitosan and 2,3-epoxypropyltrimethylammonium chloride is 30:1:6;

[0024] S2. Preparation of antibacterial fiber: 1.2 parts by weight of polydopamine nanospheres are added to 285 parts by weight of Tris buffer with a pH of 8.0, and 2.4 parts by weight of diamino polyethylene glycol are added after ultrasonic dispersion. The mixture is reacted for 28 hours under magnetic stirring to obtain an antibacterial impregnation liquid, to which 95 parts by weight of polyester fiber are added so that the fiber is completely immersed in the antibacterial impregnation liquid, and the fiber is placed for 3 hours for impregnation. After the impregnation is completed, the fiber is taken out and dried to obtain the antibacterial fiber; wherein the drying condition is: drying in a vacuum drying oven at 40° C. for 3 hours; and the ultrasonic dispersion condition is: ultrasonication at a power of 500 W for 8 minutes;

[0025] The preparation process of polydopamine nanospheres is as follows: adding anhydrous ethanol, ammonia water and deionized water into a reactor, adding dopamine hydrochloride after mixing evenly, reacting at room temperature for 32 hours and then centrifuging, repeatedly washing with deionized water until the color of the washed supernatant is close to that of deionized water to obtain polydopamine nanospheres; the volume ratio of anhydrous ethanol, ammonia water and deionized water is 4.5:0.1:11.2; the amount of dopamine hydrochloride in deionized water is 2.5 mg / mL;

[0026] S3. Spin and weave the antibacterial fiber and the antibacterial fiber together to obtain an antibacterial bandage base material, immerse it in 150 parts by weight of deionized water, add 7.2 parts by weight of concentrated ammonia water and quickly stir to mix evenly, let it stand for 28 hours, then add 116 parts by weight of 5wt% calcium chloride solution for cross-linking, absorb the calcium chloride solution after 4 hours, soak and wash with water, change the water every 3 hours, take out and dry after changing 4 times to obtain a composite fiber antibacterial bandage; the drying conditions are: drying at 45°C in a vacuum drying oven for 6 hours.

[0027] Embodiment 2

[0028] Compared with the first embodiment, this embodiment has the following differences:

[0029] In step S1, 1.2 parts by weight of sodium alginate is dissolved in 120 parts by weight of deionized water, and then 2.2 parts by weight of quaternary ammonium salt chitosan is added, and the mixture is reacted for 12 hours under magnetic stirring to obtain an antibacterial impregnation solution, and the temperature is increased to 30°C, and 55 parts by weight of cotton fiber is added thereto to completely immerse it in the antibacterial impregnation solution, and the fiber is placed for 2 hours for immersion, and after the immersion is completed, the fiber is taken out and dried to obtain an antibacterial fiber; the drying conditions are as follows: drying at 35°C in a vacuum drying oven for 2 hours; in the preparation process of quaternary ammonium salt chitosan, an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride is added, and the temperature is increased to 75°C for reaction for 25 hours, and the amount of 2,3-epoxypropyltrimethylammonium chloride in the aqueous solution of 2,3-epoxypropyltrimethylammonium chloride is 0.06 g / mL; the mass ratio of isopropanol, chitosan and 2,3-epoxypropyltrimethylammonium chloride is 28:1:4;

[0030] In step S2, 0.75 parts by weight of polydopamine nanospheres are added to 175 parts by weight of Tris buffer with a pH of 8.5, and after ultrasonic dispersion, 1.5 parts by weight of diamino polyethylene glycol are added, and the mixture is reacted for 25 hours under magnetic stirring to obtain an antibacterial impregnation liquid, to which 60 parts by weight of polyester fibers are added so that the fibers are completely immersed in the antibacterial impregnation liquid, and the fibers are placed for 2 hours for impregnation, and after the impregnation is completed, the fibers are taken out and dried to obtain antibacterial fibers; wherein the drying conditions are: drying at 35° C. in a vacuum drying oven for 2 hours; and the ultrasonic dispersion conditions are: ultrasonication at a power of 500 W for 6 minutes; wherein in the preparation process of polydopamine nanospheres, dopamine hydrochloride is added and reacted at room temperature for 28 hours, and the volume ratio of anhydrous ethanol, ammonia water, and water is 3.5:0.1:8.2; and the amount of dopamine hydrochloride in water is 2.2 mg / mL;

[0031] In step S3, the obtained antibacterial bandage base material is immersed in 95 parts by weight of deionized water, 4.5 parts by weight of concentrated ammonia water is added and the mixture is quickly stirred and mixed evenly, and after standing for 25 hours, 72 parts by weight of 5wt% calcium chloride solution is added for cross-linking, and the calcium chloride solution is absorbed after 3 hours, and the base material is soaked and washed with water. The water is changed every 2 hours, and after changing the water 3 times, the base material is taken out and dried to obtain a composite fiber antibacterial bandage; the drying conditions are: drying at 40°C in a vacuum drying oven for 4 hours.

[0032] Embodiment 3

[0033] Compared with the first embodiment, this embodiment has the following differences:

[0034] In step S1, 3 parts by weight of sodium alginate is dissolved in 280 parts by weight of deionized water, and then 5.5 parts by weight of quaternary ammonium salt chitosan is added, and the mixture is reacted for 18 hours under magnetic stirring to obtain an antibacterial impregnation solution, and the temperature is increased to 45°C, and 125 parts by weight of cotton fiber is added thereto to completely immerse it in the antibacterial impregnation solution, and the fiber is placed for 4 hours for immersion, and after the immersion is completed, the fiber is taken out and dried to obtain an antibacterial fiber; the drying conditions are as follows: drying in a vacuum drying oven at 45°C for 4 hours; in the preparation process of quaternary ammonium salt chitosan, an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride is added, and the temperature is increased to 85°C for reaction for 30 hours, and the amount of 2,3-epoxypropyltrimethylammonium chloride in the aqueous solution of 2,3-epoxypropyltrimethylammonium chloride is 0.1 g / mL; the mass ratio of isopropanol, chitosan and 2,3-epoxypropyltrimethylammonium chloride is 32:1:8;

[0035] In step S2, 1.8 parts by weight of polydopamine nanospheres are added to 425 parts by weight of Tris buffer with a pH of 8.5, and 3.6 parts by weight of diamino polyethylene glycol are added after ultrasonic dispersion. The mixture is reacted for 30 hours under magnetic stirring to obtain an antibacterial impregnation liquid, to which 145 parts by weight of polyester fiber are added so that the fiber is completely immersed in the antibacterial impregnation liquid, and the fiber is placed for 4 hours for impregnation. After the impregnation is completed, the fiber is taken out and dried to obtain an antibacterial fiber; wherein the drying condition is: drying at 45° C. in a vacuum drying oven for 4 hours; the ultrasonic dispersion condition is: ultrasonication at a power of 500 W for 10 minutes; wherein in the preparation process of the polydopamine nanospheres, dopamine hydrochloride is added and reacted at room temperature for 36 hours, and the volume ratio of anhydrous ethanol, ammonia water and water is 5.5:0.1:12.5; the amount of dopamine hydrochloride in water is 3.0 mg / mL;

[0036] In step S3, the obtained antibacterial bandage base material is immersed in 240 parts by weight of deionized water, 12 parts by weight of concentrated ammonia water is added and the mixture is quickly stirred and mixed evenly, and after standing for 30 hours, 175 parts by weight of 5wt% calcium chloride solution is added for cross-linking, the calcium chloride solution is absorbed after 5 hours, and the base material is soaked and washed with water, the water is changed every 4 hours, and after changing the water 5 times, the base material is taken out and dried to obtain a composite fiber antibacterial bandage; the drying conditions are: drying at 50°C in a vacuum drying oven for 8 hours.

[0037] Comparative Example 1

[0038] Compared with Example 1, in the preparation of antibacterial fiber, the quaternary ammonium salt chitosan is replaced with chitosan, as follows:

[0039] S1. Preparation of antibacterial fiber: 2 parts by weight of sodium alginate is dissolved in 185 parts by weight of deionized water, and then 3.5 parts by weight of chitosan is added. The mixture is reacted for 16 hours under magnetic stirring to obtain an antibacterial impregnation solution. The temperature is raised to 40°C, and 85 parts by weight of cotton fiber is added thereto to completely immerse it in the antibacterial impregnation solution. The fiber is allowed to stand for 3 hours for immersion. After the immersion is completed, the fiber is taken out and dried to obtain the antibacterial fiber. The drying conditions are as follows: drying in a vacuum drying oven at 40°C for 3 hours.

[0040] The rest is as per Example 1.

[0041] Comparative Example 2

[0042] Compared with Example 1, this comparative example does not add diamino polyethylene glycol when preparing the antibacterial fiber, as follows:

[0043] S2. Preparation of antibacterial fiber: 1.2 parts by weight of polydopamine nanospheres are added to 285 parts by weight of deionized water, and ultrasonically dispersed uniformly. The mixture is reacted for 28 hours under magnetic stirring to obtain an antibacterial impregnation liquid, to which 95 parts by weight of polyester fibers are added to completely immerse them in the antibacterial impregnation liquid, and the fibers are left to be immersed for 3 hours. After the impregnation is completed, the fibers are taken out and dried to obtain the antibacterial fiber; wherein the drying conditions are: drying at 40°C in a vacuum drying oven for 3 hours; and the ultrasonic dispersion conditions are: ultrasonication at a power of 500 W for 8 minutes.

[0044] The rest is as per Example 1.

[0045] Comparative Example 3

[0046] Compared with Example 1, this comparative example does not perform a cross-linking reaction in step S3, as follows:

[0047] S3, spinning and weaving the antibacterial fiber and the antibacterial fiber together to obtain an antibacterial bandage base material, placing the base material in a vacuum drying oven at 45° C. for 6 hours to obtain a composite antibacterial bandage.

[0048] The rest is as per Example 1.

[0049] Comparative Example 4

[0050] Compared with Example 1, the composite fiber bandage in this comparative example is obtained by directly blending cotton fiber and polyester fiber, as follows:

[0051] The preparation process of a composite fiber bandage is as follows: cotton fiber and polyester fiber are mixed and spun and woven to obtain a bandage base material, which is then placed in a vacuum drying oven and dried at 45° C. for 6 hours to obtain the composite fiber bandage.

[0052] Related tests:

[0053] The bandages prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to performance tests.

[0054] Tensile strength test: Under the conditions of 20°C and relative humidity of 65%, the sample size is 100mm long, 20mm wide and 4mm thick. The tensile properties of the sample are tested using an electronic universal material testing machine. The clamping distance is 5mm and the tensile speed is 50mm / min. Each sample is tested 5 times and the average value is taken.

[0055] In vitro cytotoxicity test: refer to ISO10993-5 "Biological evaluation of medical devices Part 5: In vitro cytotoxicity test" experimental method for testing: L-929 (ATCCCL-1) mouse fibroblasts were subcultured 5 times, seeded in 96-well plates, added with Dulbecco's modified Eagle medium, transferred to a 5% carbon dioxide cell culture incubator, kept at 37°C for 24 hours, incubated for 8 hours, added with 50μL of phenazine methyl sulfate solution, incubated at 37°C in the dark for 4 hours, and the optical density at 490nm was measured with a microplate reader to evaluate the cell proliferation. When the cell survival rate is ≥70%, the sample can be judged to be safe and non-toxic.

[0056] The test results are shown in Table 1.

[0057] Table 1 Tensile strength and in vitro cell viability test results

[0058]

[0059]

[0060] Antibacterial property test: The bandages prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were washed 0, 5, and 10 times, respectively, and then tested for antibacterial property using the GB / T 20944.2-2007 standard. The test results are shown in Table 2.

[0061] Table 2 Antibacterial test results

[0062]

[0063] The test results in Table 1 and Table 2 show that the test data of Examples 1 to 3 are better than those of Comparative Examples 1 to 4, especially Example 1 has the best performance. It can be seen from the tensile strength test results of Example 1, Comparative Example 3 (without cross-linking reaction) and Comparative Example 4 (directly woven from cotton fiber and polyester fiber) that the Ca +After cross-linking the sodium alginate coated on the antibacterial fiber and the polydopamine nanospheres coated on the antibacterial fiber, the tensile strength thereof is improved to a certain extent. This is because a macromolecular network structure is formed on the surface of the bandage through the cross-linking reaction, which further improves the tensile strength of the bandage. It can be seen from the in vitro cytotoxicity test results that the bandage prepared by the present invention has good biosafety. It can be seen from the antibacterial performance test results that the bandage prepared in Example 1 still has good antibacterial performance after multiple water washings. This is because the antibacterial agent is combined with the bandage through various methods such as covalent bonds, hydrogen bonds, and electrostatic interactions, which can effectively improve the antibacterial durability.

[0064] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0065] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a composite fiber antibacterial bandage, characterized in that: The following steps are involved: S1. Preparation of antibacterial fiber: dissolving sodium alginate in water, adding quaternary ammonium salt chitosan, mixing evenly to obtain an antibacterial impregnation liquid, adding cotton fiber to the liquid for impregnation, and taking out and drying after the impregnation to obtain the antibacterial fiber; S2. Preparation of antibacterial fiber: adding polydopamine nanospheres to a buffer solution, mixing evenly, adding diamino polyethylene glycol and stirring to obtain an antibacterial impregnation solution, adding polyester fiber to the solution for impregnation, and taking out and drying after the impregnation to obtain the antibacterial fiber; S3. Spin and weave the antibacterial fiber and the antibacterial fiber together to obtain an antibacterial bandage base material, immerse it in water, add concentrated ammonia water to mix evenly and let it stand, then add calcium chloride solution for cross-linking, wash and dry after the reaction is completed to obtain the composite fiber antibacterial bandage.

2. The method for preparing the composite fiber antibacterial bandage according to claim 1, characterized in that: In step S1, the preparation process of quaternary ammonium salt chitosan is as follows: using isopropanol as solvent, adding chitosan, heating and mixing evenly, adjusting the solution pH to 8-9, then adding 2,3-epoxypropyltrimethylammonium chloride aqueous solution, heating to 75-85°C and reacting for 25-30h, and after the reaction is completed, dialyzing, filtering and drying to obtain quaternary ammonium salt chitosan.

3. The method for preparing the composite fiber antibacterial bandage according to claim 2, characterized in that: The amount of 2,3-epoxypropyltrimethylammonium chloride in the 2,3-epoxypropyltrimethylammonium chloride aqueous solution is 0.06-0.1 g / mL.

4. The method for preparing the composite fiber antibacterial bandage according to claim 2, characterized in that: The mass ratio of isopropanol, chitosan and 2,3-epoxypropyltrimethylammonium chloride is 28-32:1:4-8.

5. The method for preparing the composite fiber antibacterial bandage according to claim 1, characterized in that: In step S2, the preparation process of polydopamine nanospheres is as follows: adding anhydrous ethanol, ammonia water and water into a reactor, adding dopamine hydrochloride after mixing evenly, reacting at room temperature for 28-36 hours, centrifuging and separating, and washing to obtain polydopamine nanospheres.

6. The method for preparing the composite fiber antibacterial bandage according to claim 5, characterized in that: The volume ratio of anhydrous ethanol, ammonia water and water is 3.5-5.5:0.1:8.2-12.

5.

7. The method for preparing the composite fiber antibacterial bandage according to claim 5, characterized in that: The dosage of dopamine hydrochloride in water is 2.2-3.0 mg / mL.

8. A composite fiber antibacterial bandage, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • An antibacterial medical bandage and its preparation method

    CN116115815B

  • A biodegradable medical polymer bandage and its preparation method

    CN117618624B

  • Antibacterial polyelectrolyte composite nanofiber membrane and preparation method thereof

    CN104083798A

  • Method for preparing slow-release antibacterial dressing

    CN105999358A

  • Method for preparing quaternary ammonium salt chitosan and polyvinyl alcohol antibacterial filter composite material

    CN109316824A

Cited By

  • Surface modified carbon fiber, preparation method thereof and application of surface modified carbon fiber in reinforced resin-based composite material

    CN116949814A

  • A surface-modified carbon fiber, its preparation method, and its application in reinforced resin-based composite materials.

    CN116949814B

  • Preparation method of mildew-proof plate

    CN121105159A